2005
DOI: 10.1027/1016-9040.10.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Temperament as Predictors of Intensity of Posttraumatic Stress Disorder Symptoms After Disaster

Abstract: Abstract. This study assesses the impact of temperament and trauma considered as predictors of Posttraumatic Stress Disorder (PTSD) symptoms experienced during flood and coal mining accidents. Five samples were studied - one comprised of coal miners who experienced a mining catastrophe (N = 52) and four samples of flood victims (N = 1041), including 562 females. PTSD symptoms were measured - depending on the sample under study - at different time periods (from 3 months to 3 years), and in two samples repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 27 publications
1
56
0
5
Order By: Relevance
“…The 1st symptom involves recurrent thoughts (flashbacks) about the traumatic event, which are a source of intensive psycho-physiological arousal, while the 2nd symptom involves avoidance of trauma-related stimuli and diminished reactions to these stimuli [20]. The results of our previous studies showed that ER and PE intensified trauma symptoms in a group of disaster victims [21], in cancer patients [22] and in HIV+ individuals [23]. Both traits, ER and PE, were also positively correlated with somatic anxiety in students [24].…”
Section: Introductionmentioning
confidence: 99%
“…The 1st symptom involves recurrent thoughts (flashbacks) about the traumatic event, which are a source of intensive psycho-physiological arousal, while the 2nd symptom involves avoidance of trauma-related stimuli and diminished reactions to these stimuli [20]. The results of our previous studies showed that ER and PE intensified trauma symptoms in a group of disaster victims [21], in cancer patients [22] and in HIV+ individuals [23]. Both traits, ER and PE, were also positively correlated with somatic anxiety in students [24].…”
Section: Introductionmentioning
confidence: 99%
“…A negative relationship between emotional reactivity and total posttraumatic growth was very likely, whereas the negative association between briskness and positive changes in relations with others was not congruent with the expectations. Emotional reactivity also allows one to predict PTSD symptoms (Oniszczenko, 2010;Strelau and Zawadzki, 2005). Additionally, emotional reactivity is a trait that shares essential variance with neuroticism, which is negatively related to growth after trauma (Linley and Joseph, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emotional reactivity appeared to be the best predictor of PTSD's intensity. Strelau & Zawadzki (2005) stress that briskness and endurance, which are related to rather chronically decreased activation levels, share some common variance with extraversion; whereas emotional reactivity reveals a positive relationship to neuroticism, which in turn is negatively related to posttraumatic growth.…”
Section: Temperament and Posttraumatic Growthmentioning
confidence: 99%
See 2 more Smart Citations